A highly effective and simplified DPWM algorithm for NPC inverters for high power factor load applications - Duc Hung Nguyen; Minh-Duc Pham; Nho Van Nguyen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
In recent years, high-power three-level neutral point clamped (NPC) inverters have significantly increased, particularly in the renewable energy sector and industries. These inverters are crucial in applications such as offshore wind farms and high-power motor drives, where reducing switching losses and improving the overall longevity, efficiency, and reliability of inverter systems are key. While conventional space vector pulse width modulation (SVPWM) has been used to reduce switching losses, it also increases the computational burden in the αβ coordinates. Our study introduces an effective and highly efficient carrier-based discontinuous pulse width modulation (DPWM) method specifically designed for high power factor loads to address this challenge. This approach significantly reduces computational execution time by adding the zero-sequence function into the fundamental signals. The efficiency of our new method is evident in the results: the proposed DPWM has successfully reduced switching losses, leading to a substantial enhancement of system efficiency. Our space vector analysis and simulation results, achieved using MATLAB and PLECS software, further validate the efficiency of our approach. Additionally, experimental results with a small-scale three-phase NPC inverter were conducted to validate the effectiveness and efficiency of the proposed DPWM.